Le Banquet de Xénophon et le Banquet de Platon : convergences et divergences - Luciana Romeri (Kentron, 2015)
Plato’s Symposium and Xenophon’s work of the same name are the first two Greek texts entirely devoted to a banquet. In both cases, a group of learned men get together at a party and talk with one another around a table after the meal while wine is served. The aim of this article, by comparing the two texts, is to identify each one’s underlying concept of conviviality. It begins with the key points on which the two texts converge, and then, considers the points on which the choices of Plato and Xenophon differ. These differences will highlight especially the different attitude of the two authors with regard to this institution of the Greek city, since in Plato’s banquet, unlike what happens in Xenophon’s, appears a clear will to protest against the traditional banquet and to criticize it.